2017
DOI: 10.1007/s10029-017-1639-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic inguinal hernioplasty after robot-assisted laparoscopic radical prostatectomy

Abstract: Laparoscopic TAPP inguinal hernia repair after RALP was safe and effective. TAPP inguinal hernia repair may be a valuable alternative to open hernioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…Three studies evaluated the surgical outcome of TAPP, and two studies evaluated the surgical outcome of TEP. The characteristics of the included studies[512131415] are showed in Table 1. All studies provided information about minor and major intra- and post-operative complications, rate of conversion to open surgery and recurrence rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies evaluated the surgical outcome of TAPP, and two studies evaluated the surgical outcome of TEP. The characteristics of the included studies[512131415] are showed in Table 1. All studies provided information about minor and major intra- and post-operative complications, rate of conversion to open surgery and recurrence rate.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias among included studies is reported in Figure 2. According to the study quality assessment of controlled intervention studies NHLBI,[7] the studies of Claus et al ,[5] Sakon et al ,[14] Wauschkuhn et al [15] were classified as ‘fair’ and the studies of Le Page et al [13] and Sakon et al [14] were classified as ‘good’. According to the GRADE approach, the quality of evidence of this meta-analysis was ‘low’.…”
Section: Resultsmentioning
confidence: 99%
“…We experienced an extremely rare complication; that is, an external iliac vein injury, during TAPP for an inguinal hernia that arose after RARP. As the number of TAPP procedures performed for inguinal hernias that occur after RARP has increased in recent years, 4,5 it is important that surgeons are able to deal with such complications. The incidence of inguinal hernias after RP for prostate cancer is said to be about 11.9%, 1 which is considered to be quite high, as the incidence of inguinal hernias in adult males is 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the HerniaSurge guidelines, many studies have been published showing the laparoscopic approach for inguinal hernias after prostatectomies [24][25][26][27][28] . There are two studies in the literature regarding robotic inguinal hernia repair after urologic procedures to our knowledge.…”
Section: Table 1 Ten Steps For a Safe Mis Inguinal Repairmentioning
confidence: 99%